PENGETAHUAN DAN SIKAP PERAWAT TENTANG PERAWATAN LUKA DI PUSKESMAS SUMBERSARI KABUPATEN PARIGI MOUTONG - Jumain; I Ketut Suastika; Sudirman (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2023)
One of the nursing services provided as a whole is wound care which must be carried out according to standard procedures. This wound care procedure aims to speed up the healing process and be free from infection. This study aims to determine the description of the knowledge and attitudes of nurses regarding wound care at the Sumbersari Health Center, Parigi Selatan District, Parigi Moutong Regency. This study used a descriptive survey design. The population in this study were all nurses who performed wound care at the Sumbersari Health Center, Parigi Selatan District, Parigi Mutong Regency, totaling 6 people and the sample used was all of the total population. Data was collected using a questionnaire and analyzed univariately. The results showed that 100% of nurses at Sumbersari Health Center, South Parigi District, Parigi Moutong Regency had good knowledge and 66.66% had good attitudes about implementing Standard Operating Procedures (SOP) for wound care. It is suggested to the Puskesmas to improve the quality of services, especially nursing practice through efforts to increase and develop the knowledge of nurses accompanied by technical training as well as education and training in modern wound care for all nurses